Serum NFL and neuropsychological performance over ∼8 years in women with and without HIV: a longitudinal repeated measures studyResearch in context - Deborah R. Gustafson; Xuantao Li; Alison E. Baird; Henrik Zetterberg; Kaj Blennow; Jinbing Zhang; Amanda Blair Spence; Pauline Maki; Anjali Sharma; Kathleen Weber; Recai Yucel (EClinicalMedicine)
Summary: Background: Blood-based biomarkers of Alzheimer's disease (AD) and stroke, including serum neurofilament light chain (sNFL), are understudied in women living with and without HIV. Methods: We assessed cross-sectional and longitudinal change in sNFL between 2008 and 2019 associated with neuropsychological performance (NP) among women living with HIV (WLWH) and without HIV (WLWOH) age ≥40 years in the Women's Interagency HIV Study. Baseline and repeated ∼8-year fasting sNFL levels were measured using Simoa. Sociodemographically-adjusted NP T-scores (attention, working memory, executive function, processing speed, learning, verbal fluency and global) were calculated. Multivariable linear regression analyses stratified by HIV serostatus examined cross-sectional baseline and follow-up associations, and ∼8-year change in sNFL level related to global and domain-specific NP T-scores. Findings: 417 participants (290 WLWH, 127 WLWOH), African American/Black (55%), ≥high school education (69%), current/former smokers (79%), and overweight/obese (BMI ≥25.0 kg/m2, 74%) were included. Compared to WLWOH at baseline, WLWH performed worse on memory and global NP. WLWH versus WLWOH had higher baseline (p ≤ 0.001) and follow-up median (p < 0.0001) sNFL levels and ∼8-year change (46.5% in WLWH versus 24.4% in WLWOH, p < 0.0001). Among WLWH, higher baseline sNFL was associated with poorer processing speed, learning, memory and verbal fluency. Among WLWOH, higher baseline sNFL was associated with poorer executive function, processing speed and verbal fluency. Among WLWH, higher follow-up sNFL was associated with poorer executive function. Among WLWOH, higher follow-up sNFL was associated with poorer executive function, processing speed, attention, memory, and global NP. ∼8-year increase in sNFL occurred in both WLWH and WLWOH and was associated with poorer executive function, processing speed, memory, and global performance at follow-up among WLWOH, and poorer executive function in WLWH. Adjustment for multiple comparisons showed associations at cross-sectional follow-up and ∼8-year increase in sNFL in WLWOH, only. Higher sNFL was associated with poorer baseline processing speed in WLWH only. Interpretation: Higher levels and greater ∼8-year increases in sNFL were associated with poorer NP by domain in WLWH and WLWOH differentially over time. Funding: The contents of this publication are solely the responsibility of the authors and do not represent the official views of the National Institutes of Health (NIH). MACS/WIHS Combined Cohort Study (MWCCS) (Principal Investigators: Bronx CRS (Kathryn Anastos, David Hanna, and Anjali Sharma), U01-HL146204; Brooklyn CRS (Deborah Gustafson and Tracey Wilson), U01-HL146202; Data Analysis and Coordination Center (Gypsyamber D'Souza, Stephen Gange and Elizabeth Topper), U01-HL146193; Chicago–Cook County CRS (Mardge Cohen and Audrey French), U01-HL146245; Northern California CRS (Bradley Aouizerat, Jennifer Price, and Phyllis Tien), U01-HL146242; Metropolitan Washington CRS (Seble Kassaye and Daniel Merenstein), U01-HL146205. The MWCCS is funded primarily by the National Heart, Lung, and Blood Institute (NHLBI), with additional co-funding from the Eunice Kennedy Shriver National Institute of Child Health and Human Development (NICHD), National Institute on Aging (NIA), National Institute of Dental and Craniofacial Research (NIDCR), National Institute of Allergy and Infectious Diseases (NIAID), National Institute of Neurological Disorders and Stroke (NINDS), National Institute of Mental Health (NIMH), National Institute on Drug Abuse (NIDA), National Institute of Nursing Research (NINR), National Cancer Institute (NCI), National Institute on Alcohol Abuse and Alcoholism (NIAAA), National Institute on Deafness and Other Communication Disorders (NIDCD), National Institute of Diabetes and Digestive and Kidney Diseases (NIDDK), National Institute on Minority Health and Health Disparities (NIMHD), and in coordination and alignment with the research priorities of the National Institutes of Health, Office of AIDS Research (OAR). MWCCS data collection is also supported by UL1-TR000004 (UCSF CTSA), UL1-TR003098 (JHU ICTR), UL1-TR001881 (UCLA CTSI).